Non-degenerate n-type doping by hydrazine treatment in metal work function engineered WSe2 field-effect transistor. (21st October 2015) - Lee, Inyeal; Rathi, Servin; Li, Lijun; Lim, Dongsuk; Atif Khan, Muhammad; Kannan, E S; Kim, Gil-Ho
Abstract: We report a facile and highly effective n-doping method using hydrazine solution to realize enhanced electron conduction in a WSe2 field-effect transistor (FET) with three different metal contacts of varying work functions—namely, Ti, Co, and Pt. Before hydrazine treatment, the Ti- and Co-contacted WSe2 FETs show weak ambipolar behaviour with electron dominant transport, whereas in the Pt-contacted WSe2 FETs, the p-type unipolar behaviour was observed with the transport dominated by holes. In the hydrazine treatment, a p-type WSe2 FET (Pt contacted) was converted to n-type with enhanced electron conduction, whereas highly n-doped properties were achieved for both Ti- and Co-contacted WSe2 FETs with on-current increasing by three orders of magnitude for Ti. All n-doped WSe2 FETs exhibited enhanced hysteresis in their transfer characteristics, which opens up the possibility of developing memories using transition metal dichalcogenides.